APLIKASI AKUAPONIK PADA KELUARGA DENGAN BALITA STUNTING DI KABUPATEN KUPANG - Lada, Christina Olly; Buntoro, Ika Febianti; Nurina, Listyawati; Turupadang, Welem (Universitas Nusa Cendana, 2022)
Stunting in toddlers occurs due to lack of nutritional intake in the long term, thus sacrificing linear growth. To meet the nutritional needs of toddlers who are growing rapidly, adequate protein intake is needed. Not all families can meet protein needs every time for daily consumption three times a day. This happens because apart from being an expensive source of protein, it also requires a storage area so that the food is not damaged. The purpose of this service is to introduce and teach the practice of making simple technology for cultivating catfish (Clarias spp.) and cultivating kangkong (Ipomoea aquatica) with an aquaponic system (by planting them in a medium bucket). Parents of toddlers learn how to do aquaponics and also provide a source of nutrition for toddlers at the household level. The results of this service indicate that there is an increase in the knowledge and skills of parents on how to make aquaponics; as well as the availability of food sources of protein and vegetables that are sufficient at any time needed for consumption by stunting toddlers.